Pharmacological inhibition of LRRK2 cellular phosphorylation sites provides insight into LRRK2 biology. (19th September 2012) - Zhao, Jing; Hermanson, Spencer B.; Carlson, Coby B.; Riddle, Steven M.; Vogel, Kurt W.; Bi, Kun; Nichols, R. Jeremy
Abstract : Mutations in LRRK2 (leucine-rich repeat kinase 2) have been linked to inherited forms of PD (Parkinson's disease). Substantial pre-clinical research and drug discovery efforts have focused on LRRK2 with the hope that small-molecule inhibitors of the enzyme may be valuable for the treatment or prevention of the onset of PD. The pathway to develop therapeutic or neuroprotective agents based on LRRK2 function (i.e. kinase activity) has been facilitated by the development of both biochemical and cell-based assays for LRRK2. LRRK2 is phosphorylated on Ser 910, Ser 935, Ser 955 and Ser 973 in the N-terminal domain of the enzyme, and these sites of phosphorylation are likely to be regulated by upstream enzymes in an LRRK2 kinase-activity-dependent manner. Knowledge of these phosphorylation sites and their regulation can be adapted to high-throughput-screening-amenable platforms. The present review describes the utilization of LRRK2 phosphorylation as indicators of enzyme inhibition, as well as how such assays can be used to deconvolute the pathways in which LRRK2 plays a role.